Depicting the politeness strategy of Tower of God’s author - Nurazizah, Enggar; Tur, Ajar Pradika Ananta; Evans, Martin Asta; Jones, Dennis Ivan (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Politeness strategy does not merely connect to reality between several persons but in imagination of one person as well like depicted in webtoons. This research contributes to give insight how to elaborate the politeness strategy expressed by one person, as author, in form of utterances. By using qualitative approach, the data were analyzed descriptively and concluded to get the line of politeness strategy. The results of the analysis in this study will be briefly describing 4 types of politeness strategy found in the conversations between the characters of the Tower of God season 1. Firstly, Bald on-record which consist of giving orders, making requests, giving warnings, and giving statements. Secondly, positive politeness which consist of seeking agreement and avoiding disagreements, making offers, promises, optimism, giving gifts (understanding and cooperation), showing flock loyalty, etc. Thirdly, negative politeness which consist of apologize for coercion, be indirect, pessimistic, minimize imposing, use questions, pay respects. Fourthly, off record which consist of ironic, vague and ambiguous, incomplete. Meanwhile, there are 4 functions found in Tower of God season 1.